From consensus to contention: Changing revenue and policy dynamics in Uganda - Anne Mette Kjær; Marianne S. Ulriksen (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper examines how the changing relationships between the Ugandan government, on the one side, and citizens and donors, on the other, affect public policy priorities. The authors hypothesize that citizens can affect governments policy priority both as voters, as represented by civil society organizations and as tax payers, whereas the influence of donors is largely driven by the extent to which the government is reliant on aid. The analysis shows how the relationships have shifted from being consensual between the government, the citizens and donors on the desirability of poverty eradication strategies and social spending, to relationships for which consensus is waning and the government is moving (back) to policies of infrastructural development and structural transformation of the economy. In the former period, donors provided the majority of funding and, with the introduction of elections, citizens preferences became an important political consideration. In the latter period, donors have lost some of their erstwhile funding dominance, the government is building new partnerships, and social sector expansion has lost much of its electoral appeal.
Keywords: 330